Browning-related oxygen depletion in an oligotrophic lake. Issue 3 (3rd July 2018) - Knoll, Lesley B.; Williamson, Craig E.; Pilla, Rachel M.; Leach, Taylor H.; Brentrup, Jennifer A.; Fisher, Thomas J.
ABSTRACT: In recent decades, terrestrial dissolved organic matter (DOM) has increased in many northeastern North American and European lakes and is contributing to long-term browning. We used a long-term dataset (1988–2014) to study the consequences of browning-related decreased water transparency on dissolved oxygen dynamics in 2 small temperate lakes in Pennsylvania, USA, that differ in their dissolved organic carbon concentrations. The oligotrophic ("clearer") lake has low productivity and historically oxygenated deep waters. The mesotrophic–slightly dystrophic ("browner") lake also has relatively low productivity but historically anoxic deep waters. We examined whether browning coincided with changes in summer dissolved oxygen dynamics, with a focus on deep-water oxygen depletion. In the clearer lake, we found that minimum oxygen concentrations decreased by ∼4.4 mg L −1 over the 27-year period, and these changes were strongly associated with both decreased water transparency and increased water column stability. We also found a shallowing of the maximum dissolved oxygen depth by ∼4.5  m and anoxic conditions established in more recent years. In the browner lake, the metrics we used did not detect any significant changes in dissolved oxygen, supporting the prediction that vertical temperature and oxygen patterns in clearer lakes may be more sensitive to increasing DOM than darker lakes. Anoxia is traditionally considered to be a consequence of anthropogenic nutrient loading and, more recently, a warming climate. We show that browning is another type of environmental change that may similarly result in anoxia in oligotrophic lakes.